Descriptive analysis of durvalumab use in unresectable stage III non-small cell lung cancer in patients treated in Quebec’s University teaching hospitals - Labrie, Valérie; Lefebvre, Judith; Labbé, Catherine; Jao, Kevin; Malick, Mandy; Simard, Serge; Bouchard, Nicole (Frontiers in Oncology, 2024)
IntroductionConsolidation durvalumab post chemo-radiotherapy (CRT) has been demonstrated to improve survival in locally advanced non-small-cell lung cancer (NSCLC). Real-world data to assess its use and impact on patients, particularly in Quebec, remain limited.MethodsWe, therefore, aimed to assess real-world durvalumab use in inoperable stage III NSCLC in Quebec, to describe progression-free survival (PFS) and overall survival (OS) outcomes as reported in the PACIFIC trial, and to evaluate safety and toxicity. Patients were retrospectively reviewed between January 1rst 2019 and December 31st 2020, based on their oncology reference date.ResultsOne hundred and eight patients treated with CRT were included, among which 82 received durvalumab (75.9%). The mean duration of treatment was 48 weeks [4-52], and 55% of patients completed the full treatment. Median PFS was 40 months in patients treated with CRT + durvalumab vs 6.9 months with CRT alone, with a hazard ratio (HR) of 0.22 (95% confidence interval (CI) 0.13-0.37; p < 0.0001). Limited access to CT scanning during the COVID pandemic, might have led to delayed disease progression detection and thus prolonged PFS. Median OS was > 52.8 months with CRT + durvalumab vs 19 months with CRT alone (HR 0.33, 95% CI 0.18-0.60; p=0.0002).DiscussionThese findings support the efficacy and safety profile of durvalumab in real-world settings.